2019
DOI: 10.1021/acsomega.9b03251
|View full text |Cite
|
Sign up to set email alerts
|

Facile Arene Ligand Exchange in p-Cymene Ruthenium(II) Complexes of Tertiary P-Chiral Ferrocenyl Phosphines

Abstract: Half-sandwich arene–metal complexes are commonly used for specific applications. Herein, we report facile arene ligand exchange reactions of two ruthenium(II) complexes of tertiary P-stereogenic ferrocenyl phosphines. By mild photochemical activation, the displacement of p-cymene and subsequent tethering by η6-coordination of the terminal phenyl ring of a biphenylyl-substituted ferrocenyl phosphine were enabled. Furthermore, the spontaneous p-cymene displacement in a 2-methoxyphenyl-containing ferrocenyl phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 68 publications
2
20
0
Order By: Relevance
“…[75][76][77] Adduct [1a(BH 3 ) 3 ] was found to crystallise with crystallographic C 3 symmetry (space group R 3, Fig. 1) and compares well (Table S5 †) to structural parameters of similar ferrocenyl-phosphane boranes described by us 78 as well as byŠtěpnička and co-workers. 79 Recently we reported the capability of 1c to bind coinage metal ions in a tridentate trigonal planar coordination mode; 43 now we have turned our focus to potential trinuclear gold(I) complexes of 1a-c.…”
Section: Preparation and Electrochemical Characterisation Of Trisphossupporting
confidence: 71%
“…[75][76][77] Adduct [1a(BH 3 ) 3 ] was found to crystallise with crystallographic C 3 symmetry (space group R 3, Fig. 1) and compares well (Table S5 †) to structural parameters of similar ferrocenyl-phosphane boranes described by us 78 as well as byŠtěpnička and co-workers. 79 Recently we reported the capability of 1c to bind coinage metal ions in a tridentate trigonal planar coordination mode; 43 now we have turned our focus to potential trinuclear gold(I) complexes of 1a-c.…”
Section: Preparation and Electrochemical Characterisation Of Trisphossupporting
confidence: 71%
“…Recently, we prepared three P-stereogenic ferrocenyl phosphine boranes 2a-c-ML with a 4-methoxyphenyl substituent in the 1′-position of the ferrocenyl group (Scheme 1). [67,68] In these monomeric (non-dendritic) ligands (ML) the 4-methoxyphenyl substituent serves to mimic the phenol linker which is needed in immobilization reactions. The P-stereogenic ferrocenyl phosphine boranes 2a-c-ML were synthesized with excellent enantiopurity (> 95 % ee in all cases) and subsequent borane-deprotection by heating in diethylamine, followed by reaction with [{Ru(p-cymene)Cl 2 } 2 ], yielded the monomeric ruthenium complexes 3a-c-ML-Ru.…”
Section: Synthesis Of P-stereogenic Ferrocenyl Phosphinesmentioning
confidence: 99%
“…The P ‐stereogenic ferrocenyl phosphine boranes 1 a – c were successfully synthesized from an unsymmetrically disubstituted 1,1′‐ferrocene and three methyl (phenyl)phosphinite boranes (Scheme ) which were accessible via an (−)‐ephedrine‐based oxazaphospholidine borane complex . This auxiliary‐based methodology provides a convenient strategy for a stepwise preparation of tertiary P ‐stereogenic phosphines (>95 % ee in all cases).…”
Section: Methodsmentioning
confidence: 99%
“…The first indications that made us investigate the phosphorus‐based stereochemistry of these ligands in detail were the single crystal X‐ray crystallographic analyses of their corresponding ruthenium(II) complexes 3 a – c (Figure ). In repeated attempts, we continuously found that complexes 3 a and 3 b crystallize in the achiral space group P true1 indicating the presence of racemates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation